PERBANDINGAN LIKUIDITAS SAHAM SEBELUM DAN SESUDAH PERUBAHAN FRAKSI HARGA DAN SATUAN PERDAGANGAN - Dony Darma Putra Irawan, I Kadek; Agung Suaryana, I Gusti Ngurah (E-Jurnal Akuntansi; Vol 14 No 2 (2016), 2016)
On January 6, 2014, the Indonesian Stock Exchange (IDX) implements a new tick size and lot size. This study aims to examine difference in liquidity around the date of adoption of Decree No. KEP-00071/BEI/1-2013 . Purposive sampling technique was use for sampling, in order to obtain 90 samples. Observation period is on 5 days before and after the date. The resulted data were carried out on statistically analysis using paired sample t-test. The results indicated a difference in the averages of  trading volume activity before and after the application of the new tick size and lot size, after the event period has shown there are increasing of trading volume activity averages. The results showed that the application of the new rules able to increase stock liquidity, which means the expectation of  Indonesia Stock Exchange successfully achieved.
Keywords: tick size, lot size, trading volume activity